Language and Gender in The Soap Opera “Suara Hati Seorang Isteri” (SHSI) - Aslamiyah, Suaibatul (Getpress Management Journals, 2024)
This study examines language and gender with a focus on the soap opera “Suara Hati Seorang Isteri” (SHSI). The focus of the research is on the differences between man and woman in the number of speeches and the number of turns to speak between man and woman. The research method uses a combination of qualitative and quantitative. The research findings of the number of men’s talk with a percentage of 70.9% and women’s percentage of 29.1%. while men occupy a higher level of 70.9% and 68.7%. While women obtained a percentage of 29.1% and 31.3%